Net zero energy buildings : international projects of carbon neutrality in buildings - Voss, Karsten, ....-; Musall, Eike, ....- (München : Institut für internationale Architektur-Dokumentation, 2011)
Net-zero energy buildings, equilibrium buildings, or carbon-neutral citiesdepending on location and underlying agenda, the statistics vary. The variety of terms in use indicates that a scientific method is still lackingwhich poses a problem not just in regard to international communication, but also with respect to planning processes as a response to energy challenges. The clarification and meaning of the most important terms in use is extremely important for their implementation. Since October 2008 a panel of experts from an international energy agency has concerned itself with these topics as part of a project entitled Toward Net Zero Energy Solar Buildings. The objective is to analyze exemplary buildings that are near a zero-energy balance in order to develop methods and tools for the planning, design, and operation of such buildings. The results are documented in this publication. More than just a showcase presentation of select projects, the focus of this publication is on relaying knowledge and experience gained by planners and builders. Even if many questions remain unanswered, project examples that have already been implemented prove on a practical basis that the objective of a zero-energy balance is already attainable today.
Keywords: Architectuur; Buildings -- Energy consumption; Duurzaam bouwen; Ecologisch bouwen; Kwaliteitssystemen; Renewable energy sources